A Phenomenological Analysis of Divorced Women’s Experiences with Multiple Sexual Relationships After Divorce - Esfandiari , Maliheh; Honarparvaran , Nazanin (Psychology of Woman Journal, 2026)
Objective: The objective of this study was to explore and analyze the lived experiences of divorced women who engage in multiple sexual relationships after divorce, focusing on psychological, social, familial, economic, and identity-related dimensions.Methods and Materials: This research employed a qualitative phenomenological design to capture the subjective meanings of participants’ post-divorce experiences. Ten divorced women attending a family counseling clinic in Shiraz were recruited through purposive sampling, based on criteria including at least one year since divorce, a history of multiple sexual relationships, and willingness to share personal experiences. Data were collected through semi-structured in-depth interviews, complemented by field notes and document analysis. Data analysis followed Strauss and Corbin’s grounded theory methodology, involving open, axial, and selective coding. Trustworthiness was ensured through prolonged engagement, member checking, peer debriefing, and maintaining an audit trail. Ethical principles of informed consent, confidentiality, and participant autonomy were strictly observed.Findings: The analysis revealed six overarching dimensions shaping the experiences of divorced women: (1) psychological and emotional struggles characterized by loneliness, ambivalence, and fear of judgment; (2) social and cultural pressures involving stigma, secrecy, and value conflicts; (3) identity and gender redefinition, including proving femininity, asserting independence, and exercising control over sexuality; (4) familial dynamics, such as estrangement, concealment from relatives, and concern about children; (5) economic realities, with experiences of both dependency and empowerment through financial independence; and (6) coping strategies and personal reconstruction, including spiritual practices, counseling, journaling, and efforts to build healthier relationships.Conclusion: The study underscores that divorced women’s engagement in multiple sexual relationships is a multifaceted phenomenon shaped by intersecting psychological, social, familial, cultural, and economic forces. These experiences reveal both vulnerability and resilience, emphasizing the need for supportive interventions, culturally sensitive counseling, and policies that reduce stigma while fostering autonomy and well-being.